Drinking Water’s Consumption in West Borneo’s Peatlands Area: Causal Factors of Caries? - Sri Rezki; Irma HY Siregar; Halimah Halimah (Jurnal Kesehatan Gigi, 2022)
West Borneo has 1.73 million hectares of peatland areas. Therefore, people consume drinking water derived from rainwater or mountain water. In line with that, they also have a high caries rate. This water consumption might have a role in caries incidence. Besides, substrate, agent, host, and time could become other influence factors. This study aims to determine the factors that affect dental caries in West Borneo’s peat areas based on drinking water consumption.The research method was the facto exposé research. The population was children aged 12-14 years and taken by Cluster random sampling. The data were analyzed with correlation tests related to drinking water consumption which causing dental caries numbers.The study showed a significant difference in the Fluoride content of the four water types (p-value = 0.018).The influence of water consumption on caries was only 2%. However, the caries incidence among respondents who consumed mountain water was higher.Behavioral and tooth brushing activities significantly impacted respondents with different drinking water consumption.